2014
DOI: 10.1371/journal.ppat.1004286
|View full text |Cite
|
Sign up to set email alerts
|

A Screen of Coxiella burnetii Mutants Reveals Important Roles for Dot/Icm Effectors and Host Autophagy in Vacuole Biogenesis

Abstract: Coxiella burnetii is an intracellular pathogen that replicates in a lysosome-derived vacuole. The molecular mechanisms used by this bacterium to create a pathogen-occupied vacuole remain largely unknown. Here, we conducted a visual screen on an arrayed library of C. burnetii NMII transposon insertion mutants to identify genes required for biogenesis of a mature Coxiella-containing vacuole (CCV). Mutants defective in Dot/Icm secretion system function or the PmrAB regulatory system were incapable of intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
269
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(294 citation statements)
references
References 73 publications
(96 reference statements)
12
269
1
3
Order By: Relevance
“…Consistent with previous studies, this multi-vacuole phenotype was also observed when expression of STX17 (syntaxin 17) was silenced to block autophagy progression [13,24] (Figure 1(c)). STX17 is responsible for facilitating fusion of autophagosomes with lysosomes [25].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with previous studies, this multi-vacuole phenotype was also observed when expression of STX17 (syntaxin 17) was silenced to block autophagy progression [13,24] (Figure 1(c)). STX17 is responsible for facilitating fusion of autophagosomes with lysosomes [25].…”
Section: Resultssupporting
confidence: 90%
“…In addition to having only one large CCV per cell, a normal Coxiella infection of HeLa cells results in recruitment of LC3B to the lumen of the CCV, representing significant fusion of the CCV with autophagosomes [13,15]. The multi-vacuole phenotype observed above is indicative of a CCV fusion defect in the absence of CLTC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations